Corporate Governance and Merger and Acquisition Foreign Direct Investment: Firm-level Evidence from Japanese Foreign Direct Investment into the US - Joseph D. Alba; Donghyun Park; Peiming Wang (Asian Development Bank (ADB), 2009)
Merger and acquisition (M&A) is a mechanism for promoting corporate governance suggesting that an improvement in overall corporate governance may have a negative effect on M&A activity. Since M&A foreign direct investment (FDI) is a cross-border variant of M&A, stronger corporate governance may also reduce M&A FDI. Hence, we use firm-level evidence from Japanese FDI into the United States to investigate the effect of US corporate governance on Japanese M&A FDI. Our results indicate that two landmark corporate governance regulations by the US Securities and Exchange Commission in 1992 contributed significantly to the sharp decline in Japanese M&A FDI in the US during the 1990s. Our evidence lends some support to the notion that corporate governance may affect not only domestic M&A activity but also cross-border M&A activity. Our study also sheds light on the puzzle of why Japanese FDI into the US fell during the 1990s despite the depreciation of the US dollar.
hdl:11540/1795
Keywords: F21; F23; G21; 330; Corporate governance; Merger and acquisition; FDI; Corporate Governance; Übernahme; Auslandsinvestition; Japanisch; USA